Japanese language learning with social media - Bakhautdinova, G N (Journal of Oriental Studies, 2016)
The learning has steadily grown over the last 5 years since the appearance of sites Busuu, Italki, livemocha, Voxswap etc. This article focuses on the use of one such site, called Lang-8, and the ways learners of Japanese as a foreign language construct their own learning environment, by managing their online identities to form cooperative language learning opportunities.